Entry by Foreign Firms in the United States Under Exchange Rate Uncertainty - Campa, Jose Manuel (The Review of Economics and Statistics, 1993)
This paper tests the effects that real exchange-rate fluctuations had on foreign direct investment into the United States during the 1980s. Using a sample of foreign investments in sixty-one four-digit SIC U.S. wholesale industries, this paper finds exchange-rate volatility to be negatively correlated with the number of foreign investments that occur in these industries. This negative effect is most pronounced for industries where sunk investments in physical and intangible assets are relatively high. Although exchange rate volatility deters investment from all countries, its effect was most significant for investments by Japanese companies. Copyright 1993 by MIT Press.